Concomitant Alpha- and Gamma-Sarcoglycan Deficiencies in a Turkish Boy with a Novel Deletion in the Alpha-Sarcoglycan Gene. (22nd June 2014) - Diniz, Gulden; Tosun Yildirim, Hulya; Gokben, Sarenur; Serdaroglu, Gul; Hazan, Filiz; Yararbas, Kanay; Tukun, Ajlan
Abstract : Limb-girdle muscular dystrophy type 2D (LGMD-2D) is caused by autosomal recessive defects in the alpha-sarcoglycan gene located on chromosome 17q21. In this study, we present a child with alpha-sarcoglycanopathy and describe a novel deletion in the alpha-sarcoglycan gene. A 5-year-old boy had a very high serum creatinine phosphokinase level, which was determined incidentally, and a negative molecular test for the dystrophin gene. Muscle biopsy showed dystrophic features. Immunohistochemistry showed that there was diminished expression of alpha- and gamma-sarcoglycans. DNA analysis revealed a novel 7 bp homozygous deletion in exon 3 of the alpha-sarcoglycan gene. His parents were consanguineous heterozygous carriers of the same deletion. We believe this is the first confirmed case of primary alpha-sarcoglycanopathy with a novel deletion in Turkey. In addition, this study demonstrated that both muscle biopsy and DNA analysis remain important methods for the differential diagnosis of muscular dystrophies because dystrophinopathies and sarcoglycanopathies are so similar.